Implementasi Metode Pandan Wangi pada Penguasaan Kemampuan Membaca Al-Qur’an di MI Al-Ikhlas Kauman Parakan Temanggung - Neli Agustina; Fatkhurrohman Fatkhurrohman; Ali Mu’tafi (STIKes Ibnu Sina Ajibarang, 2025)
The learning process of reading the Qur'an for students at MI Al-Ikhlas Kauman Parakan when learning using the Pandan Wangi method is considered to have run very well and is very helpful in supporting the Qur'an reading program. This is proven by the average student test score of 96.25 by meeting 3 indicators, namely correctness, fluency and eloquence, so it is proven that using the Pandan Wangi method book can help master the ability to read the Qur'an. Students have a high enthusiasm for learning and good use of learning media.